2009
DOI: 10.1038/ejhg.2009.40
|View full text |Cite
|
Sign up to set email alerts
|

Goltz–Gorlin (focal dermal hypoplasia) and the microphthalmia with linear skin defects (MLS) syndrome: no evidence of genetic overlap

Abstract: Focal dermal hypoplasia (FDH) is an X-linked developmental disorder with male lethality characterized by patchy dermal hypoplasia, skeletal and dental malformations, and microphthalmia or anophthalmia. Recently, heterozygous loss-of-function mutations in the PORCN gene have been described to cause FDH. FDH shows some clinical overlap with the microphthalmia with linear skin defects (MLS) syndrome, another X-linked male lethal condition, associated with mutations of HCCS in the majority of cases. We performed D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 26 publications
5
28
0
Order By: Relevance
“…Indeed, mosaicism for mutations causing autosomal or X-linked dominant disorders may result in segmental presentation of some clinical features (as described above), typical but milder findings, a classical phenotype, or even no apparent phenotype [Gripp et al, 2006;Harmsen et al, 2009]. The two reported individuals and our patient with somatic mosaicism for the HRAS alteration highlight the different phenotypic outcomes in these cases and illustrate the importance of genetic testing in patients with an atypical phenotype.…”
Section: Discussionmentioning
confidence: 63%
“…Indeed, mosaicism for mutations causing autosomal or X-linked dominant disorders may result in segmental presentation of some clinical features (as described above), typical but milder findings, a classical phenotype, or even no apparent phenotype [Gripp et al, 2006;Harmsen et al, 2009]. The two reported individuals and our patient with somatic mosaicism for the HRAS alteration highlight the different phenotypic outcomes in these cases and illustrate the importance of genetic testing in patients with an atypical phenotype.…”
Section: Discussionmentioning
confidence: 63%
“…Grzeschlik et al [2007] described a patient with classical Goltz-Gorlin syndrome, manifestations being linear skin lesion, syndactyly, asymmetric bone defects and dental defects. The phenotype in the patient with the R243X mutation described by Harmsen et al [2009] had a severe, lethal phenotype: linear skin lesion, syndactyly of both hands and feet, malformed ears, iris coloboma, omphalocele, and hypoplastic left heart. The present patient has classical, severe Goltz-Gorlin syndrome and in addition four main signs of Cantrell (-Haller-Ravitsch) syndrome, which were absent in the earlier reported patients with the same mutation.…”
Section: Discussionmentioning
confidence: 98%
“…The c.727C>T (R243X) mutation has been reported twice before [Grzeschlik et al, 2007;Harmsen et al, 2009]. Grzeschlik et al [2007] described a patient with classical Goltz-Gorlin syndrome, manifestations being linear skin lesion, syndactyly, asymmetric bone defects and dental defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenic PORCN variants have previously been reported that affect the same transmembrane domain, which further supports the pathogenicity of the p.(Gly157Asp) variant. 5,[19][20][21] Variants in PORCN were first reported as a cause of FDH in 2007. 19, 22 Froyen et al later identified PORCN variants and gene deletions in a cohort of patients with a clinical diagnosis of FDH.…”
Section: Discussionmentioning
confidence: 99%